Effect of Applied Voltage on Spectroscopic Characterization of Neon Plasma - Mutar, Shihab A.; Abbas, Ibrahim K.; Aadim, Kadhim A. (Iraqi Journal of Science, 2024)
In this work, the glow spectrum from a neon strip lamp, used in homes and all private places, was diagnosed using optical emission spectroscopy (OES), to measure plasma parameters from spectral data (electrons density, electrons temperature, plasma frequency, Debye length). The intensity of the emission spectrum increases with increasing the applied voltage (100-220V). A spectral diagnosis was made of the cold plasma generated by the neon glow system where the glow spectrum produced was prepared for the diagnosis at variable alternating voltages that begin to rise gradually. The diagnosis was made at atmospheric pressure and room temperature of 27 ̊C. The results showed a gradual increase in the intensity of the neon spectrum generated by the system with the amount of gradual increase in the applied voltage. Between (250-850) nm, the behavior of neon spectral lines varied between high and low spectral intensity peaks.